New protocol for early robot-assisted gait training after spinal surgery - Jee, Sanghyun; Jang, Chan Woong; Shin, Sang Hoon; Kim, Yeji; Park, Jung Hyun (Frontiers in Medicine, 2024)
Early rehabilitation post-spinal surgery is vital for patients' recovery. Robot-assisted gait training (RAGT) shows promise but requires further study to establish a specific protocol and gauge its effects on both patients and physical therapists. This study aimed to determine the impact of a newly developed protocol for early RAGT on patients' functional enhancement and satisfaction levels after spinal surgery, as well as on the physical therapists who implemented the therapy.First, we developed the protocol in collaboration with three physiatrists and two physical therapists with extensive experience in musculoskeletal rehabilitation. The protocol was updated three times, each after three rounds of face-to-face meetings. Afterward, we conducted a cross-sectional study involving five physical therapists and 32 post-spinal surgery patients at a tertiary hospital rehabilitation center. The intervention consisted of five sessions of RAGT. Main outcome measures included the Functional Ambulation Category (FAC), the ambulation item of the Modified Barthel Index (MBI ambulation), and satisfaction surveys for both patients and physical therapists.RAGT typically started 17.91 ± 9.76 days postoperatively and was successfully applied with no remarkable adverse effects. The FAC scores increased from 2.65 ± 1.21 to 3.78 ± 0.71 (p = 0.006), and MBI ambulation increased from 7.69 ± 2.71 to 10.66 ± 2.90 (p < 0.001) between transfer and discharge. Satisfaction with the robot, RAGT, and treatment, assessed using a 5-point Likert scale, were 3.30 ± 0.79, 3.72 ± 0.85, and 3.08 ± 0.84, respectively. Satisfaction was notably the highest for alleviating fear of falling, whereas managing pain and discomfort during position changes scored the lowest. Physical therapists rated RAGT satisfaction, impact on the working environment, and treatment stability at 3.0 ± 0.65, 2.80 ± 0.67, and 3.50 ± 0.61, respectively.Early spinal surgery rehabilitation with RAGT improved patients' functionality and gait satisfaction. While physical therapists considered RAGT safe, its impact on their work environment was limited. Integrating RAGT into post-spinal surgery rehabilitation demands ongoing protocol refinement, custom robot development, and efficacy evaluations.